OPTIMALISASI TANAMAN KAKAO DI DESA SELELOS KECAMATAN GANGGA KABUPATEN LOMBOK UTARA MELALUI PENGENDALIAN HAMA DAN PENYAKIT SERTA PEMBUATAN PUPUK KOMPOS DARI LIMBAH KAKAOWISATA MATA AIR MEDJET DI DESA SELELOS KECEMATAMAN GANGGA KABUPATEN LOMBOK UTARA - Jannah, Fista Fathul; Scabra, Andre Rachmat; Mantika, Ayu Aras; Fidhun, Muhammad; Ummam, Khatibul (Universitas Mataram, 2024)
Agriculture serves as the mainstay of the economy in North Lombok Regency because the majority of its population works in the agricultural sector. The community service program bt Mataram University, focused in Selelos Village, Gangga District, is one of the villages where most of the population works as cocoa farmers. The aim of this program is to address various issues related to pest and diseases control in cocoa plants in Selelos Village in order to increase cocoa productivity. The analyzed issues include the lack of awareness among cocoa farmers about the importance of caring for cocoa plants through various GAP (Guaranteed Asset Protection) practices such as pruning, fertilizing, and sanitation. Additionally, cocoa pod husk waste in the plantation is also a contributing factor to spread of diseases and pests as well as environmental pollution. Efforts by Mataram University student involve direct mentoring of farmers in collaboration with PT OFI (Olam Food Ingredients) and managing cocoa husk waste into compost fertilizer that can be reused bt farmers. Through these activities, the community can better care of cocoa plants, resulting in maximum hervest yields. The compost from cocoa husk waste can be reused by darmers to maximize farm output.